Fast‐and‐Giant Photorheological Effect in a Liquid Crystal Dimer. Issue 9 (8th April 2019) - Aya, Satoshi; Salamon, Péter; Paterson, Daniel A.; Storey, John M. D.; Imrie, Corrie T.; Araoka, Fumito; Jákli, Antal; Buka, Ágnes
Abstract: Mechanically responsive organic materials can change their viscoelastic properties in response to external stimuli. However, materials that exhibit highly contrasting viscoelastic properties coupled with fast and reversible switching between the states involved have remained elusive. Here, it is shown that a nonsymmetric photoresponsive liquid crystal dimer exhibits photoswitching of its viscoelastic properties (shear viscosity, storage, and loss moduli) with remarkable contrast of up to 10 6 while transitioning between crystal and nematic phases. This switching is reversible and takes less than 100 s for both forward ( trans ‐ cis photoisomerization) and backward ( cis ‐ trans photoisomerization) reactions due to the coexistence of two allotropes containing two types of stereoisomers. This combination of highly contrasting viscoelastic behavior with fast and reversible switching establishes a whole new performance level for mechanically responsive organic materials and offers very considerable application potential in such diverse areas as photoswitchable adhesives, in vibration control, and as novel brakes. Abstract : Fast mechanical switch : Fast and giant photorheological effects are found in a liquid crystal dimer via crystal–liquid/liquid–crystal photomelting and crystallization processes.